EFL STUDENTS’ ENTHUSIASM ON LEARNING GIVING ADVICES MATERIAL THROUGH ICE BREAKER - Gina Sonia; Testiana Deni Wijayatiningsih; Dodi Mulyadi; Muhimatul Ifadah; Siti Aimah; Riana Eka Budiastuti; Dian Candra Prasetyanti; Anjar Setiawan; Chattaphorn Sriprasert (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
In this pandemic Covid 19 situation, students and teachers must adapt with the new era in teaching learning process. Online learning requires many students to study more diligently in order to comprehend the material, such as providing advices. Additionally, the monotonous and teachercentred learning process bores more than 50% of students, causing them to lose interest in teaching and learning activities. The objective of this study is to describe the students' enthusiasm for implementing icebreaker activities after they learned how to give advice. This study used a descriptive quantitative method. The students' enthusiasm indicators administered eleven questions. The result indicated that there is a positive response to their enthusiasm, which can help them develop their critical thinking when it comes to learning English, particularly when it comes to providing advice materials. To summarize, this current research sheds new light on how to manage students' enthusiasm for English materials during synchronous and asynchronous teaching-learning interactions.Keywords: students‟ enthusiasm, ice breaker, giving advices